Da literatura distópica à dispersão dos enunciados do presente: uma análise discursiva dos mecanismos de poder no controle da sociedade - Oliveira, Rafael Camargo de (2018)
This study aims to analyze the functioning of power technologies used to control the bodies of individuals and populations. In order to do so, it was necessary to articulate discourse, power and knowledge through discourse analysis, with emphasis on the theoretical assumptions of Michel Foucault. This work is about an analysis of the power tecnologies used to control the population and the body of individuals. To do this, it was necessary to articulate discourse, power and knowledge through discourse analysis, with emphasis on the theoretical assumptions of Michel Foucault. Our route also includes the approximations and displacements of a sovereign power to the disciplinary power, present in the eighteenth century, to biopower, which is found in the late nineteenth and early twentieth century. For the analysis we use the works Brave New World, by Aldous Huxley; 1984, by George Orwell; and We by Evgueny Zamiatin together with various present-day statements so that we can draw a parallel between the practices present in the works and those experienced today in our daily lives. The problematization of the forms of power in analysis passes through the relation of biopolitics with neoliberalism, sovereign right and the excesses of biopower; for a discussion of the notion of state racism, of resistance, when considering Foucault's dialogues with Hannah Arendt and the concept of biopolitics in Agamben and the devices of language, family, security, sexuality, and happiness.